Efektivitas Audiovisual dan Booklet sebagai Media Edukasi untuk Meningkatkan Perilaku Skrining IVA - Veronica Silalahi; Mohammad Hakimi; Wiwin Lismidiati (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Cervical cancer is the caused of high maternal mortality. Prevention of cervical cancer done by screeningVisual Inspection with Acetic Acid (IVA). The objective of this study to analyzed the effectiveness of health educationapplying health belief model using audiovisual and booklet on female behavior for IVA examination in thework area of Pacarkeling Public Health Center. The research method used Quasi Experimental with Design Non-Equivalent Control Group Design. Research subjects were women aged 30-50 years who have never done previousIVA examination. Sample selection using cluster sampling technique with sample of 79 respondents for each groupof intervention and control group. Health education using audiovisual and booklet. Data analyzed using wilcoxontest, chi-square, mann-whitney, and linear regression. Health education using audiovisual and booklet effectivein improving the behavior of respondents for IVA screening. Increased of knowledge, attitudes, health belief of theintervention group is greater than control group. The behavior of women in IVA screening for intervention groupwas greater than control group after intervention. External variables such as age, education, occupation, income,previous information have an effect on behavior improvement. Health education is effective in improving womenbehavior for IVA screening